Volume 4: Manufacturing Materials and Metallurgy; Ceramics; Structures and Dynamics; Controls, Diagnostics and Instrumentation; 1997
DOI: 10.1115/97-gt-427
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Industrial Gas Turbine Experience With Second Generation Single Crystal Alloy Turbine Blades

Abstract: The rhenium containing second generation single crystal alloy CMSX-4® was introduced for turbine blading in the Solar® Turbines Incorporated Mars® T-14000 engine in 1990. Based on the initial success with the first 4,000 hour engine test, the alloy was confirmed as bill of material for the stage 1 turbine blades in the T-14000 engine. Field experience has been excellent and there are now about 1,500,000 hours total accumulated engine time with several engines having completed their first overhaul cycle (Typica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…CMSX-4 alloy has been successfully used in numerous aero and industrial gas turbine applications since 1991. These applications, such as high pressure turbine blades and seals, have demonstrated an impressive combination of high temperature strength, good phase stability and oxidation, hot corrosion and coating performance in extensive engine service [11,12,13]. Close to five million pounds (650 heats) of CMSX-4 alloy have been manufactured to date.…”
Section: Cmsx-4 (Sls)[la + Y] Alloymentioning
confidence: 99%
“…CMSX-4 alloy has been successfully used in numerous aero and industrial gas turbine applications since 1991. These applications, such as high pressure turbine blades and seals, have demonstrated an impressive combination of high temperature strength, good phase stability and oxidation, hot corrosion and coating performance in extensive engine service [11,12,13]. Close to five million pounds (650 heats) of CMSX-4 alloy have been manufactured to date.…”
Section: Cmsx-4 (Sls)[la + Y] Alloymentioning
confidence: 99%
“…Only very limited distress has been noted in the CMSX-4 airfoils after testing and the engine results indicate that the relative improvement for CMSX-4 is perhaps greater than originally anticipated. This has been particularly true for the multi-airfoil segmented 2nd vane (Burkholder, et al, 1995); (Figs. 13-17 incl.)…”
Section: Allison Engine Test Resultsmentioning
confidence: 83%
“…Solara Turbines, Inc. has reported that six years of field experience for CMSX-4 first stage blades in the MARS 100 industrial turbine has been excellent Total running time for the 132 engines in the field is 1.25 million hrs, with the blades and Pal coatings in good condition when examined at engine overall after 26,000 -28,000 Firs service. The MARS 100 engines tend to spend at least 50% of their miming time at maximum power with natural gas or liquid natural gas (LNG) as the predominant fuel (Harris, et al, 1992, Kubarych and Autrecoechea, 1993, Brentnall, et al, 1997. Figure 29 shows a photomicrograph from a MARS 100 first stage CM5X-4 turbine blade after over 25,000 service hours.…”
Section: : Other Engine Experiencementioning
confidence: 99%
See 1 more Smart Citation